Corneal alterations in Crisponi/CISS1 syndrome: A slit-lamp biomicroscopy and in vivo confocal microscopy corneal report. (2nd January 2017) - Agresta, Antonio; Fasciani, Romina; Padua, Luca; Petroni, Sergio; La Torraca, Ilaria; Dickmann, Anna; Zampino, Giuseppe; Caporossi, Aldo
ABSTRACT: Background : Mutations in the cytokine receptor-like factor 1 (CRLF1) gene are responsible for Crisponi/Cold-induced Sweat Syndrome, an extremely rare autosomal-recessive multisystem disorder. The protein encoded is a soluble cytokine receptor, involved in the ciliary neurotrophic factor receptor (CNTFR) pathway. The ciliary neurotrophic factor (CNTF) promotes corneal wound healing and patients with Crisponi/CISS1 syndrome suffer from recurrent keratitis. The aim of the study was to report and discuss the corneal alterations in Crisponi/CISS1 rare disease. Materials and methods : We evaluated the cornea of both eyes in four Crisponi/CISS1 patients to provide a detailed description of slit-lamp biomicroscopy findings. Corneal sensitivity, tears functionality and blinking video recording at rest were also assessed in all patients. Two patients were also evaluated with in vivo confocal microscopy, completed with a needle electromyography of their orbicularis muscles. Results : None of the patients presented a tears dysfunction and video recording documented a prolonged lid excursion in all patients. Slit lamp examination revealed a chronic epithelial impairment in all cases. Needle electromyography of the orbicularis oculi showed a dystonic pattern. The confocal microscopy confirmed the biomicroscopic observed lesions and documented unusual findings of the corneal nerve plexus. Conclusions : This is the first report of microscopic cornea alterations explored with confocal imaging in Crisponi/CISS1 patients. The observed corneal findings suggest a possible direct correlation to the CNTFR pathway defect and the blinking imbalance could exacerbate the compromised epithelial wound healing. Topical administrations of lubricating eye drops are strongly recommended in these patients.